ANTECEDENT FINTECH CONTINUANCE INTENTION IN MANADO (CASE STUDY: GOPAY) - Mandagi, Calvin; Lapian, S L. H. V. J,; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
The rapid development of information technology (IT) has brought various new innovations and one of them is financial technology (Fintech). The presence of Fintech has brought a revolution in the financial industry. The rapid development of Fintech is supported by fundamentals based on population breakdown, unbanked population, Internet, and smartphone penetration. Indonesia is one of the countries in Southeast Asia that has rapid development of Fintech, where the development of Fintech in Indonesia is supported by the internet users in Indonesia currently reaching 175.4 million with penetration reaching 64 percent and 98 percent of these internet users using smartphones to access the internet. The purpose of this study is to understand the factors that influence Fintech continuance intention based on the perceived benefit, perceived risk, and trust of the users. Respondents used in this study were 130 samples and tested using PLS-SEM (Partial Least Square - Structural Equation Modeling). The results reveal that perceived benefit, perceived risk, and trust have a significant influence on Fintech continuance intention, where perceived benefit has the strongest effect while perceived risk has the weakest effect on Fintech continuance intention.Â Keyword: fintech, perceived benefit, perceived risk, trust, continuance intention